Hygiene and Sanitation Practices in Bar Section at Oyster Dealer Beach Haus Batu Belig, Kerobokan Kelod, Kuta Utara, Badung, Bali - Setiawan, I Made Thio; Wiantara, I Gusti Nyoman; Widhiastuty, Ni Luh Putu Sri (LPPM Universitas Dhyana Pura, 2026)
The bar section of a beach house establishment faces unique hygiene and sanitation challenges due to its semi-open environment, high-intensity operations, and direct product-consumer contact. This study aims to analyze the implementation of hygiene and sanitation practices in the bar section of Oyster Dealer Beach Haus Batu Belig, Kuta Utara, Badung, Bali; identify the challenges encountered; and describe the efforts made to overcome them. A qualitative descriptive approach was used with data collected through direct observation using a structured checklist covering SOP compliance, personal hygiene, beverage hygiene, environmental hygiene, and bar equipment hygiene, in-depth interviews with the Bar Manager and Bartender, and documentation during January–May 2025. The results show that hygiene and sanitation practices have been implemented with sufficient consistency across all five dimensions. SOP compliance was generally observed although inconsistencies arose during peak hours. Personal hygiene was well maintained, including handwashing, clean uniforms, and FIFO-based ingredient storage. Challenges included inconsistent SOP adherence under operational pressure, some staff not wearing hand gloves during busy shifts, pre-mixing of certain drinks, drainage blockage from garnish residue, and rapid equipment reuse without optimal cleaning. Mitigation efforts include daily briefings, twice-weekly personal hygiene training, task delegation during peak hours, twice-weekly general cleaning, and provision of additional bar equipment to reduce rapid reuse. This study concludes that hygiene and sanitation standards at the bar section require continuous supervision and capacity building to achieve consistent compliance.The bar section of a beach house establishment faces unique hygiene and sanitation challenges due to its semi-open environment, high-intensity operations, and direct product-consumer contact. This study aims to analyze the implementation of hygiene and sanitation practices in the bar section of Oyster Dealer Beach Haus Batu Belig, Kuta Utara, Badung, Bali; identify the challenges encountered; and describe the efforts made to overcome them. A qualitative descriptive approach was used with data collected through direct observation using a structured checklist covering SOP compliance, personal hygiene, beverage hygiene, environmental hygiene, and bar equipment hygiene, in-depth interviews with the Bar Manager and Bartender, and documentation during January–May 2025. The results show that hygiene and sanitation practices have been implemented with sufficient consistency across all five dimensions. SOP compliance was generally observed although inconsistencies arose during peak hours. Personal hygiene was well maintained, including handwashing, clean uniforms, and FIFO-based ingredient storage. Challenges included inconsistent SOP adherence under operational pressure, some staff not wearing hand gloves during busy shifts, pre-mixing of certain drinks, drainage blockage from garnish residue, and rapid equipment reuse without optimal cleaning. Mitigation efforts include daily briefings, twice-weekly personal hygiene training, task delegation during peak hours, twice-weekly general cleaning, and provision of additional bar equipment to reduce rapid reuse. This study concludes that hygiene and sanitation standards at the bar section require continuous supervision and capacity building to achieve consistent compliance.